Testing theoretical assumptions underlying the relation between anxiety, mind wandering, and task-switching: A diffusion model analysis - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2022)
Despite the well-documented negative effects of anxiety on task-switching (switch costs), few studies have directly tested major theoretical assumptions about (a) the specific processing component of task-switching that is impaired by anxiety, (b) anxious individuals’ strategies during task-switching, and (c) the mediating role of mind wandering in the relation between anxiety and task-switching. We addressed these issues using a stochastic diffusion model analysis and novel thought-probe technique in the task-switching paradigm. Our results suggest that the locus of impaired switch costs under state anxiety lies in the efficiency of task-set reconfiguration and not in proactive interference processing. Moreover, state anxiety was associated with impaired mixing costs, which are another crucial index of task-switching. We found only partial evidence for anxious individuals’ proneness to compensatory strategies during task-switching. However, no evidence was found for a mediating role of task-unrelated thoughts and a moderating role of working memory in the relation between anxiety and task-switching. Our findings elucidate theoretical assumptions underlying anxiety and cognitive functioning.